PERAN DESA ADAT DALAM PENGENDALIAN PEMANFAATAN LAHAN DI DESA JATILUWIH, BALI - Arimbawa, Wahyudi (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 3 (2016): Oktober 2016DO - 10.24843/JRS.2016.v03.i03.p02, 2016)
Jatiluwih has been included in Unesco's (United Nations) World Heritage List for sometime now. It has since has gone through dramatic changes in land use, from a sleepy village dominated by its paddy fields into a crowded tourist destination. The development of extensive tourist amenities has since become apparent. While this development has contributed to the local economy, investors, and government, it has raised concerns of the balance between economic development and social development as a whole. In this context the study of the potential played by the desa adat institution in controlling land utilization in Jatiluwih Village is examined. It uses a conceptual approach proposed by Chapin, Godschalk and Kaiser in 1957, in which land use control is systematically examined within a three tiered process. The first mechanism involves the identification of interests and their determining roles. The second mechanism is to recognize the rules that direct the game played by each interest; and the third is the management governing land use changes of Jatiluwih . The final objective of this study is to develop a system of land use management for this village. In order to embrace local interests, this system must incorporate the preservation of agricultural land and the tradition-based practices embedded within it, including the subak (the traditional irrigation system) and the implications it holds for change. Keywords : desa adat; land use control; Desa Jatiluwih Abstrak Sejak Jatiluwih telah ditetapkan sebagai Warisan Budaya Dunia dari Unesco, terjadi perubahan pemanfataan lahan secara dramatik, dari lahan tidur yang didominasi oleh persawahan menjadi suatu daerah tujuan wisata yang padat. Pembangunan fasilitas pariwisata tampak jelas dan semakin bertambah. Ketika pembangunan ini telah berkontribusi kepada ekonomi lokal, investor, dan pemerintah, kondisi ini telah mengembangkan keseimbangan antara pembangunan  ekonomi dan sosial. Dalam konteks ini, kajian instusi dengan desa adat dalam mengontrol pemanfaatan lahan di Desa Jatiluwih perlu diuji. Dengan menggunakan pendekatan konsepsual Chapin, Godschalk dan Kaiser (1957), aspek pengendalian pemanfaatan lahan dikaji secara sistematis berdasarkan tiga tindakan substansial. Pertama, mengidentifikasikan berbagai kepentingan dan karakternya; Kedua, menentukan mekanisme permainan; Ketiga, manajemen yang mengatur perubahan tata guna lahan. Hasil akhir yang diperoleh adalah kesuksesan dalam manajemen pengendalian pemanfaatan lahan di Desa Jatiluwih. Studi ini secara kontekstual didasarkan pada tantangan untuk mempertahankan eksistensi lahan pertanian serta sistem religi didalamnya yaitu subak. Pada kondisi yang sama, kebutuhan untuk mengakomodasi perkembangan industri kepariwisataan juga merupakan sisi yang penting bagi peningkatan taraf kehidupan masyarakat.
Keywords: desa adat, pengendalian pemanfaatan lahan, Desa Jatiluwih